Sustainability of small scale carciniculture in areas of low hydrical demand (Research, Society and Development, 2020)
Reducing the availability of water resources has made many activities unfeasible. When we can develop an activity that can meet social needs and generate income, with little technology and using the minimum amount of water, we can say that this activity becomes viable and sustainable. Shrimp farming can be one of these activities if implemented responsibly. This activity has shown to be a strong alternative in the production of food, helping to supply the growing world demand. Given this importance, the objective of this study was to analyze and evaluate the level of sustainability of shrimp farming under social, technological, environmental and economic aspects in the community of Cajueiro - Aracati - CE. Using as methodology to obtain data and information characteristic of the community, the application of questionnaires, site visits and analysis of technical reports for family producers, from January to April 2017. Sustainability was evaluated in stages, using indicators to each case. Where we can conclude that: families presented critical social level, managed to produce with little technology, using few natural resources and correctly, and made the activity economically viable.